Early and multiple-loci divergency of proper and common names: An event-related potential investigation. (October 2018) - Sulpizio, Simone; Job, Remo
Abstract: We investigated how the brain represents and processes proper and common names by measuring event-related brain potentials (ERPs) while participants performed a lexical decision task. We capitalized on the fact that in Italian proper names require an upper-case initial letter. Stimuli were either in their typical (proper names with upper-case letter and common names with lower-case letter, Teresa, matita 'pencil') or atypical/less frequent written format (proper names with lower-case letter and upper-case with upper-case letter, teresa, Matita ). Results showed effects on both early and late negativities (N100 and N400) and early and late positivities (P200 and Late Positivity). Interestingly, the positivities showed an interaction between orthographic typicality and name category, while negativities were associated with letter case independently of name category (N100), or with category membership independently of case (N400). Our results indicate that the brain detects the difference between proper and common names early on and tracks this distinction at different points in time during processing. Highlights: We investigated processes proper and common name representation by means of ERPs. A lexical decision task in Italian, with names in upper- and lower-case first letter. The difference between proper and common name emerged at the P2, N4, Late Positivity. Proper and common names differ at the level of orthographic and semantic processing.